Pelatihan Dan Pengembangan Media Pembelajaran Dori (Ludo Surili) Berbasis Ekoliterasi Dengan Memanfaatkan Limbah Industri Rumah Tangga Kain Perca di Desa Langonsari Kabupaten Bandung - Nopi Krisnawati; Salis Elmadani; Tazqia Aulia Rahmawati; Maulana Yusuf; Maulana Ramdani; Fitri Nuraeni (Abdi Wiralodra : Jurnal Pengabdian Kepada Masyarakat, 2022)
There are potentials and problems that occur in Langonsari Village, namely patchwork waste originating from the UMKM industry and waste can be used as potential, one of which is as a learning media material. With the problem of waste, elementary school students must be able to recognize and have a caring attitude towards the environment which is often called ecoliteracy and the development and training of learning media must continue to be carried out both for teachers and the community. One example of learning media is DORI (Ludo Surili) which is adapted from Ludo but has a different size. The research subjects consisted of training for partners and development for 16 elementary school students who were divided into 4 groups. Data collection techniques are observation, questionnaire, pre-test and post-test. The learning media development techniques consist of: (1) the planning phase, (2) the preparation phase, (3) the implementation phase and (4) the evaluation phase. The results of the study on the effectiveness of learning media showed that with a percentage of 97.463 in the very good category, while the results of the pre-test and post-test showed that the average value had increased, both individually or as a whole, the increase showed that the pre-test was at number 42, 7 and on the post-test at 68.2 so that students are able to understand the material given with DORI learning media.